THE DEVELOPMENT OF NATIONAL LINGUISTIC PERSONALITY THROUGH HUMANITIES - Галина Груць (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article analyses the problem of linguistic personality development by means of Humanities, as well as scientists' view on the role of native language in the development of personality's spiritual culture. The essence of the concept "linguistic personality" has been characterized in this paper. There has been grounded the statement, that the residents of eastern regions of Ukraine are being 'mankurtised'. The author elaborates on the semantic meaning of the words 'honour', 'dignity', 'education'. It has been grounded, that an important factor in development of a linguistic personality is the formation of future specialists' beliefs in the fact, that mental and spiritual health of a country depends on responsible attitude to a word as national code. Examples of mental difference between Ukrainian and Russian, and the results of student survey regarding the necessity of developing linguistic personality have been presented in the article.